RNA interference of an orthologue of Dicer of Meloidogyne incognita alludes to the gene’s importance in nematode development - Sadia Iqbal (Nature Portfolio, 2021)
Abstract Dicers and dicer-like enzymes play an essential role in small RNA processing in eukaryotes. Nematodes are thought to encode one dicer, DCR-1; only that for Caenorhabditis spp. is well-characterised. Using genomic sequences of eight root-knot nematodes (Meloidogyne spp.), we identified putative coding sequences typical of eukaryotic DICERS. We noted that the primary and secondary structures of DICERS they encode were different for different Meloidogyne species and even for isolates of the same species, suggesting paralogy for the gene. One of the genes for M. incognita (Midcr-1.1) expressed in eggs, juvenile stage 2 and adults, with the highest expression in the adult females. All the Meloidogyne DICERS had seven major domains typical of those for Caenorhabditis spp. and humans with very similar protein folding. RNAi of Midcr-1.1 in J2s using seven dsRNAs, each based on sequences encoding the domains, induced mild paralysis but measurable knockdown was detected in J2s treated with five of the dsRNAs. For four of the dsRNAs, the RNAi effect lasted and reduced the nematode’s infectivity. Also, host plant delivery of dsRNAs complementary to coding sequences of the Dicer Dimerisation domain impaired development, reducing nematode infection by 71%. These results confirm the importance of the gene to nematode health.